Interpretation of Subsurface Structure Based on the Magnetic Data at Semurup Geothermal Area Kerinci - Ikhwan Fikri Maulidan; Ratika Tri Suci; Andre Mahendra; Ardian Putra (Universitas Andalas, 2021)
The interpretation of subsurface structures in Semurup geothermal area has been carried out using the geomagnetic method. Data were collected in an area of 1500 m Ã— 1400 m consisting of 160 points. The magnetic anomaly value obtained was derived from the total magnetic induction value that has been corrected by IGRF and diurnal variation, then transformed by reduction to equator and upward continuation to remove noise and separate local and regional anomalies. The results of data processing showed the total magnetic field values in the study area ranged from -1730.4 nT to 1909.0 nT. Magnetic anomalies in this study area are dominated by negative values that may be caused by demagnetised rocks (a result of hydrothermal alteration). The results of 2D modeling, it has 5 rock layers that can be classified into 3 main parts of the geothermal system The first and second layers are caprock with a depth of up to 850 meters consisting of sedimentary rock, clay, and sandstone. The third layer is indicated as a reservoir with a depth from 850 to 1450 m and is dominated by sandstone and clay alteration Hot rock in the fourth and fifth layers is dominated by basalt igneous rock and the presence of dacitic lava intrusion from the northeast of the study area at depths below 1450 m, and the Siulak fault as a outflow zone for geothermal fluid. The presence of the caprock, reservoir, hot rock, and fault zones indicates that the Semurup area has geothermal potential and is suitable for further exploration.